The Role of Family Resilience in Enhancing Family Communication Among Generation Z - Zamralita, Zamralita; Wilis, Anastasia Putri Leleng; Angelina, Stephanie; Fahlevi, Reza (Universitas Medan Area, 2025)
Generation Z is the dominant demographic group in Indonesia and is widely known as digital natives, having grown up in the era of digital communication. Their communication patterns tend to prioritize efficiency and are largely visual based; however, this can negatively impact the quality of direct, face-to-face family interactions. A lack of in-person communication increases the risk of excessive internet use and contributes to mental health issues. Effective family communication plays a crucial role in supporting adolescents’ psychological well-being, and one of the key contributing factors is family resilience. Family resilience encompasses belief systems, organizational processes, and communication processes within the family. This study aims to examine the influence of family resilience on family communication among Generation Z in Indonesia. A quantitative approach was employed using convenience sampling, involving 210 participants. The instruments used were the Family Communication Scale (FCS) and the Walsh Family Resilience Questionnaire (WFRQ). The analysis revealed a significant positive correlation between family resilience and family communication (R² = 0.84). These findings suggest that stronger family resilience contributes to better family communication quality and may help reduce family conflicts and the negative impacts of excessive technology use.